A case report of optic nerve head tuberculosis - M Periyanayagi (TNOA Journal of Ophthalmic Science and Research, 2018)
The purpose of this article is to present a rare manifestation of ocular tuberculosis (TB). Here, we present a case of a 19-year-old female who came to our department with defective vision in the left eye (LE) for 20 days which was insidious in onset and progressive in nature. The visual acuity in the affected eye was 2/60. Anterior segment examination of both eyes was normal. Fundus examination of LE showed active papillitis with macular edema. Fundus fluorescein angiography showed optic nerve hyperfluorescence with leakage and macular edema in the LE. All other investigations were found to be within normal limits except QuantiFERON-TB Gold and Mantoux which showed an induration of 19 mm. The patient was presumed to be a case of TB of optic nerve head and started on antituberculous therapy. She showed a rapid response to the treatment and her visual acuity improved to 6/9 at the end of 2 months.